The Relationship Between Nutritional Status and The Incidence of Dysmenorrhea in Adolescent Women - Iis, Iis; Rohaeni, Ela (Riviera Publishing, 2022)
The incidence of dysmenorrhea in the world is substantial; on average more than 50% of women in every country experience menstrual pain. One of the factors that can cause dysmenorrhea is nutritional status. A person's nutritional status depends on nutritional intake and needs. If the nutritional intake and body needs are balanced, it will result in good nutritional status. This study aimed to determine the relationship between nutritional status and the incidence of dysmenorrhea in midwifery students at STIKes Cirebon. The research method is an analytic design using a Cross Sectional approach. The population in this study used a total sampling technique, namely, all 36 Midwifery students. Data was taken using a questionnaire and then analyzed using chi-square with a confidence level of = 0.05. The results showed a relationship between nutritional status and the incidence of dysmenorrhea, where the P value was 0.003. Results P value <0.05, meaning there is a significant relationship between nutritional status and the incidence of dysmenorrhea. Based on the study's results, it was found that 28 people (77.8%) had experienced dysmenorrhea and 8 (22.2%). Thus, most respondents experienced the incidence of dysmenorrhea. It is recommended that adolescents pay more attention to their nutritional needs regularly to reduce the incidence of dysmenorrhea during menstruation